The Effect of Different Planning Conditions versus Explicit Grammar Instruction on Young EFL Learners’ Oral Production of a Picture Promoted Task and Grammar Gain - Karim Sadeghi; Azadeh Hamidi (Revista de Lingüística y Lenguas Aplicadas)
This study examined the effects of three task conditions on young EFL learners’ oral performance of a picture prompted task and their grammatical knowledge gain. To this end, 34 EFL learners were randomly assigned into three experimental groups, namely online planning, pre-planning, and explicit instruction, and one control group. Pictures were employed as prompts to implement the tasks in all groups. A Grammatical Judgment Test was used to compare students’ knowledge of simple present passive structure before and after the treatment. Learners’ oral task performance was measured in terms of Complexity, Accuracy, and Fluency (CAF). The findings demonstrated significant differences among groups as for CAF measures. However, no significant differences were spotted in GJT posttest scores. The paper calls for the incorporation of diverse prompt-based planning conditions in task-oriented teaching practices in order to target learners'  higher levels of oral competence.